BRAND LOYALITY DI TINJAU DARI TRUST DAN BRAND EQUITY PADA KENTUCKY FRIED CHICKEN (KFC) KOTA PROBOLINGGO - Junaidi, Junaidi; Nafis, M. Raihan Wishal; E, Syarif Hidayatullah; Dewi, Dessy Kristiana (Bussman Journal : Indonesian Journal of Business and Management, 2021)
The study is conducted on purpose to identify whether there is a significant influence of brand trust and brand equity on brand loyalty at KFC Probolinggo City or not. This study employed a quantitative approach which was a causal associative method. Besides, this study consisted of three variables which were brand trust (X1), brand equity (X2), and brand loyalty (Y). The study also used 10,030 populations and a sample of 263 respondents which applied a 10% error. The study employed non-probability sampling which was a purposive sampling as a sampling technique. As a result, based on the partial hypothesis testing, the testing result on the brand trust variable (X1) toward the brand loyalty variable (Y) obtains the score of tvalue>ttable (6.442>1.650735) and the significance score is 0.000<0.05. On the other hand, the testing result of the brand equity variable (X2) on the brand royalty variable (Y) obtains the score of tvalue>ttable (11.984>1.650735) and the significance score is 0.000<0.05. It can be concluded that there is a significant influence of brand trust and brand equity on brand loyalty at KFC Probolinggo City